2013
DOI: 10.1080/07359683.2013.844015
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Patient Satisfaction With Public Hospital Services

Abstract: The aim of this research is to propose and test a model of the causal relationships among the constructs of perceived service quality, consumption emotions, and satisfaction among users of public hospital services. The conceptual model proposed in this study postulates that: (a) perceived service quality is positively related to positive emotions and negatively related to negative emotions; (b) perceived service quality is positively related to patient satisfaction; and (c) positive emotions are positively rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 42 publications
0
36
1
Order By: Relevance
“…40 It also refers whether the services adhere to standards and norms of clinical diagnoses and treatments. 26 We found 30 studies 1,3,4,1012,15,23,26,27,40,45,49,50,55,57,58,60,71,75,83,85,87,90,110,114,115,117,127,128 providing evidence that better technical care may have played an important role in increased patient satisfaction level. Among them, eight studies 10,12,27,45,114,115,129 identified that perceived competency of health professionals had one of the most significant impact on the variations in patient satisfaction.…”
Section: Resultsmentioning
confidence: 93%
“…40 It also refers whether the services adhere to standards and norms of clinical diagnoses and treatments. 26 We found 30 studies 1,3,4,1012,15,23,26,27,40,45,49,50,55,57,58,60,71,75,83,85,87,90,110,114,115,117,127,128 providing evidence that better technical care may have played an important role in increased patient satisfaction level. Among them, eight studies 10,12,27,45,114,115,129 identified that perceived competency of health professionals had one of the most significant impact on the variations in patient satisfaction.…”
Section: Resultsmentioning
confidence: 93%
“…The importance of the excitement factors increases when their performance is high, but they become unimportant when they underperform. The three-factor theory has been tested in different service settings such as: tourism Back, 2012;Caber, Albayrak, & Matzler, 2012;Coghlan, 2012;Füller et al, 2006;Mikulić & Prebežac, 2011); hospitality (Albayrak & Caber, 2014;Chang, Chen, & Hsu, 2010;Lee & Min 2013); e-commerce/mobile telecommunication services (Busacca & Padula, 2005;Caber, Albayrak, & Loiacono, 2013;Pezeshki, Mousavi, & Grant, 2009); B2B/retailing services (Arbore & Busacca, 2009;Matzler, Bailom, Hinterhuber, Renzl, & Pichler, 2004;Stan et al, 2007;Staus & Becker, 2012); and transportation (airline/airport) (Kuo & Jou, 2014;Mikulić & Prebežac, 2008). All these studies have shown important practical implications of the three-factor theory, such as organisational changes towards better service delivery and efficient budget allocation through better service improvements' prioritisation.…”
Section: Service Attributes' Performance and Patient Satisfactionmentioning
confidence: 97%
“…Analysts may choose to emphasize the impact of available information (James and Moseley 2014;Marvel 2016), self-centred utility maximization (Jensen and Andersen 2015), emotions (Ladhari and Rigaux-Bricmont 2013), a sense of identity (Jlike et al 2014), the unconscious tendency towards conformity (Sanders and Canel 2015) or the level of physical involvement with services under review (Loeffler 2016). In the end, it can be difficult to understand whether subconscious identification as a member of a group (Sanders and Canel 2015) interacts with, for instance, selfinterest (Jensen and Andersen 2015), leading to a specific set of reasons why a given service user (dis)likes a specific public service.…”
Section: User Satisfaction For Inclusive Public Policymentioning
confidence: 99%
“…or the opinions of organization managers (Sanders and Canel 2015;Andersen and Hjortskov 2016). According to existing studies of citizen satisfaction, the nature of public opinion is determined by several factors, including the ways in which citizens use public services (Brown 2007;Van Ryzin and Charbonneau 2010;Im et al 2012;Ladhari and Rigaux-Bricmont 2013;Pierre and Røiseland 2016), their involvement in providing such services (Scott and Vitartas 2008;Sanders and Canel 2015;Taylor 2015), and their held-out knowledge, beliefs (Brown 2007;Harding 2012;Ladhari and Rigaux-Bricmont 2013;Barrows et al 2016) and emotions (Lawton and Macaulay 2013;Ma 2017). A continuous analysis of citizen preferences will help managers of public institutions make decisions that align with public needs (Walker and Boyne 2009)).…”
mentioning
confidence: 99%